Insulin Degludec: Pharmacokinetics in Patients with Renal Impairment - Kiss, István (Springer International Publishing, 2013)
BACKGROUND: Insulin degludec is a new-generation basal insulin with an ultra-long duration of action. We evaluated the pharmacokinetic properties of insulin degludec in subjects with normal renal function; mild, moderate or severe renal impairment; or end-stage renal disease (ESRD) undergoing hemodialysis. METHODS: Thirty subjects (n = 6 per group) received a single subcutaneous dose of 0.4 U/kg insulin degludec. Blood samples up to 120 h post-dose and fractionated urine samples were collected. RESULTS: The ultra-long pharmacokinetic properties of insulin degludec were preserved in subjects with renal impairment, with no statistically significant differences in absorption or clearance, compared with subjects with normal renal function. In subjects with ESRD, pharmacokinetic parameters were similar whether the insulin degludec pharmacokinetic assessment period included hemodialysis or not, and total exposure was comparable to subjects with normal renal function. Simulated mean steady-state pharmacokinetic profiles were comparable between groups. CONCLUSION: This study indicated dose adjustments due to impaired renal function should not be required for insulin degludec.